Pengelolaan Pasar Milik Pemerintah Kabupaten Bekasi Berbasis Kemitraan Perumda - Rizky Afnan Fadillah; Melfinna; Ferry Mardihardjo D (Bekasi Development Innovation Journal, 2024)
ABSTRACT Each market has varying building areas, parking lots, kiosks, stalls, vendors, and visitors. The problems and challenges faced are also quite diverse, depending on the conditions and environment of each market. However, from the initial information and observations, it is clear that in general, the market management owned by the Bekasi Regency Government still faces many problems and challenges, so that the management carried out has not produced the desired results. Some of the identified problems include: (1) The lack of commitment and integrity of market human resources in managing the market professionally; (2) The absence of standardized market management in Bekasi Regency; (3) The suboptimal empowerment of business actors in market management; and (4) The lack of systematic legalization of market management in Bekasi Regency. Based on the conditions, opportunities, and market problems presented above, it is important to conduct a study on Market Management in Collaboration with Regional-Owned Enterprises and/or Established as Regional-Owned Enterprises (Perumda). The results of this study are needed to improve market management, which is closely related to strengthening the trade sector, serving community needs, and increasing the sources of revenue for Bekasi Regency in the future. Keywords: market, perumda